Analysis of Enzyme Kinetic Data - Bowden Athel Cornish (OXFORD UNIVERSITY PRESS, 1955)
This text introduces the theory behind the statistical analysis of kinetic data for enzyme-catalyzed reactions in the steady state. It includes a detailed description of the use of the LEONORA program for analyzing enzyme kinetic data.